Diseño de adaptación de un motor eléctrico fuera de borda alimentado por energía solar fotovoltaica para una embarcación de 16 ft de eslora. (2021)
In places of tourist affluence, such as Lake Tota, where the main attraction includes navigation, it is convenient to look for energy alternatives that help preserve the natural environment, reduce costs and continue providing quality services to tourists. The main purpose of this research was the design and adaptation of an outboard electric motor powered by photovoltaic solar energy for a 16-foot (4.85 m) naval aluminum boat with capacity for eight passengers, propelled by a 2238 W electric motor at 24 VDC, powered by 24 V and 370 W polycrystalline solar panels. The respective calculations of materials and equipment were made under the parameters and regulations on navigation (National Statute of Fluvial Navigation of the Ministry of Public Works and Transport, today Ministry of Transport) adopted by Decree No. 2689 of 1988, taking into account the "STANDARDS FOR THE CONSTRUCTION, INSPECTION AND CLASSIFICATION OF FLUVIAL VESSELS of the American Bureau of Shipping 1956. At the end of the design calculations, it was found necessary to install 2 solar panels of 370 W each, in order to cover the optimum photovoltaic power of 0.74 KW. Likewise, the characteristics of the necessary outboard electric motor were established, which is a Torqeedo Travel 1103 CL, with a power of 2.238 KW (3.0 HP), transmission length of 0.508 m, weight of 17.7 Kg, integrated Lithium Ion battery of 922 Wh and a Maximum total weight of load, boat and equipment of 0.750 Ton (750Kg). On the other hand, the corresponding schemes, plans and diagrams of the electrical design were elaborated. Finally, the cost calculations of materials and labor for the construction of the design, which range from 21'443.700 COP, are provided.